Estimating the interaction between a storm surge and a tide - Quynh, Do Ngoc; Viet Lien, Nguyen Thi; Manh, Dinh Van (Vietnam Journal of Mechanics, 1996)
In the paper the using numerical hydro dynamical model for the researching the non-linear interaction between a storm surge and a tide in the Gulf of Tonkin, where the storm surge and the tide are of the same rank in value is presented. The results of calculating denote that the interaction lowers a total sear level at high tide and rises a total sea-level at low tide.